Managing Diabetes Mellitus in Chronic Kidney Disease: Approaches - Akram, Muhammad; Maqbool, Tahmina; Hasan, Mohammed Khudhair; Abdulghafoor, Hind A.; Khan, Fahad Said; Sołowski, Gaweł; Umaru, Isaac John (Darul Yasin Al Sys, 2025)
The main objective of this article is to review the medical management of the disease known as “diabetes mellitus” and its general consequences. To assess the risks and benefits of intensive glycemic control in patients with diabetic kidney disease, the search was refined using the following specific terms: “diabetic nephropathy” and “kidney disease”, as well as “diabetes management” and “antidiabetic agents” or “oral hypoglycemic agents”. A unique challenge. Due to changes in insulin production, glucose transport and metabolism, impaired renal function is associated with hyperglycemia and hypoglycemia. Management of hyperglycemia is more difficult in patients with diabetic nephropathy, which often requires a change in the treatment regimen. When changing diabetes medications and insulin regimens, healthcare teams responsible for the care of these patients must be vigilant and organized to make such changes.